Thermal and optical characterization of up-converting thermographic phosphor polymer composite films. (8th June 2018) - Sabri, Firouzeh; Allison, Stephen W; Aryal, Makunda; Collins, Josh; Bell, Howard
Abstract: Up-converting thermographic phosphors are of significant interest due to specific advantages for temperature measurement applications over traditional contact-based methods. Typically, infrared excitation stimulates visible fluorescence only from the target phosphor and not the surrounding medium. This is in contrast to ultraviolet excitation which may also produce interfering luminescence from cells and other biological tissue in the vicinity, for instance. When traversing a material, usually infrared losses due to scattering and absorption are less than for ultraviolet wavelengths. An example is human skin. This investigation follows logically from earlier efforts incorporating thermographic phosphors into elastomers and aerogels and their function as a reusable temperature sensor has been previously demonstrated by the authors. Layered phosphor/PDMS/aerogel composites are also currently under investigation by the authors for heat flux sensing. For maximum utility and understanding; physical, optical and thermal properties are characterized over a wide range of temperatures. Y2 O2 S:Yb, Er and La2 O2 S:Yb, Er up-converting phosphor composites with a fixed doping concentration were synthesized for this study and fully characterized as a function of temperature. The excitation/ emission characteristics of the powder alone and the prepared composites were investigated between -50 °C and +200 °C in an environmental chamber and the decay behavior of each sample type was measured. Here, the authors report on decay behavior and emission intensity of the PDMS composites as a function of temperature. Results were compared with powder –only parameters and are reported here.